Stable excess mortality in a multiple sclerosis cohort diagnosed 1970–2010 - Sumelahti, Marja-Liisa; Verkko, A.; Kytö, Ville.; Sipilä, Jussi O. T. (Wiley, 2025)
Background and purpose
Multiple sclerosis (MS) is associated with excess mortality. The use of disease-modifying treatments (DMTs) has recently been associated with survival benefits.
Methods
A regional MS database was linked with national registries. People with MS (pwMS) diagnosed in 1971–2010 were included and followed up until the end of the year 2019. Five matched controls were acquired for every person with MS. DMTs included in the analyses were interferon and glatiramer acetate.
Results
Median follow-up time of the 1795 pwMS was 20.0 years (range 0.1–48.7 years). Survival did not differ between decades of diagnosis (p = 0.20). Amongst pwMS, male sex (adjusted hazard ratio [aHR] 1.70; 95% confidence interval [CI] 1.41–2.06), higher age at diagnosis (aHR 1.83; 95% CI 1.65–2.03 per 10-year increment) and primary progressive disease course (aHR 1.29; 95% CI 1.04–1.60) were independently associated with poorer survival. DMT use was associated with better survival (p < 0.0001) and better survival during follow-up (aHR 0.56; 95% CI 0.38–0.81). Compared to matched controls, median life expectancy was 8–9 years shorter in pwMS with survival diverging from controls during the first decade after diagnosis, more clearly in men than women.
Conclusion
Despite DMT use being associated with better survival, relative life expectancy of pwMS did not change over five decades in Western Finland. Male sex was an independent risk factor for death amongst pwMS, but excess mortality was higher in women. More work and methods are needed to improve survival in pwMS.